THE INFLUENCE OF WORK ENVIRONMENT AND COMMUNICATION ON EMPLOYEE PERFORMANCE ON CV. INDO JAVA LAND - Reni Armiati (Program Studi Perbankan Syari'ah Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2020)
One of the beverage business that can be said is currently on the rise is CV. Indo Javaland. The purpose of this study was to determine how much to know the effect of the work environment and communication on employee performance on the CV. Indo Javaland by using the SPSS 22 program, namely the classical assumption test method, simple and multiple regression analysis, simple and multiple correlation analysis, and hypothesis testing t, f test, and the coefficient of determination. The results of the research with the hypothesis t test show that the work environment (X1) and communication (X2) variables partially have a significant and positive effect on employee performance (Y). From the results of the calculation of the F test also shows that the work environment (X1) and communication (X2) simultaneously significantly and positively affect employee performance (Y). While the determination of the coefficient of determination can be found that is equal to 0.589 which means that the work environment (X2) and communication (X1) has a contribution of 58.9% of employee performance (Y), while the remaining 41.1% is contributed by other factors that are not included in the research variables by researchers.